A Study of Correlation between Crack Initiation during Dynamic Wear Process and Fatigue Crack Growth of Reinforced Rubber Materials. (5th May 2015) - Euchler, Eric; Kratina, Ondrej; Stoček, Radek; Gehde, Michael
Abstract : The aim of this study is concentrated on the experimental investigation of crack initiation during dynamic wear process and its correlation with fatigue crack growth of reinforced rubber materials. The analyzed rubber compounds suitable for applications such as treads for truck tires were based on natural rubber (NR) and polybutadiene rubber (BR). The dynamic wear behavior has been studied using an own developed testing equipment based on gravimetric determination of mass loss of test specimen. Fatigue crack growth (FCG) analysis was performed under pulse loading in accordance with real dynamic loading conditions of rolling tires using the Tear Analyser (TA). We show the crack initiation process during dynamic wear with respect to different impact energies and correlate the liability of crack initiation with FCG data at given tearing energy as a function of the rubber compositions. We demonstrate the higher crack initiation resistance of rubber blends with increased content of BR, while a predominant influence of NR improves the resistance against crack propagation especially at higher strain levels due to strain induced crystallization.